Glos polskich i niemieckich nacjonalistów w debacie na temat integracji europejskiej - Kosman, Michał; Malendowicz, Paweł (Rocznik Integracji Europejskiej, 2015)
The subject of this paper is nationalism as a direction of political thinking, where the idea of the nation is the dominant principle. The main Polish nationalist political parties of the recent 25 years include: National Revival of Poland, Polish National Community and National Party „Szczerbiec”. The main German nationalist political parties include: National Democratic Party of Germany, The Republicans, The Right, Pro NRW (North Rhine-Westphalia). Far-right parties in Poland and in Germany are against the European Union and the process of European integration. The nationalist parties in Europe fear economic and cultural globalisation, multicultural- ism, immigrants, Islam, materialism and consumerism that – in their opinion – threaten their respective nations.